PERSEPSI PETANI KARET TERHADAP PENDIDIKAN ANAK DI DESA KAMPUNG BARU KECAMATAN KUPITAN KABUPATEN SIJUNJUNG - Ningsih, Fitria Yuda; Zusmelia, Zusmelia; Zulfa, Zulfa (Pendidikan Sejarah, 2014)
Generally rubber farmer in Kampung Baru has low background knowledge, it is caused by several of community in Kampung Baru did not continue their study on high level. To create nationality life that has high background knowledge from a generation to other generation, of course it will be a important problem, especially on rubber farmer perfection on their child education. The result of this research shown that society perception toward education in someoneâs life was not same. It can be seen that there is a different opinion. There is a someone who gave a judgment that someone standard of living improvement just can be reached from the knowledge which they got from education. In other side there is another opinion which said that standard of living improvement is gotten by the effort and hard working without education that they got at school. From the research, the researcher found that there were 15 rubber farmer became researcherâs informant, there are 10 people (66,67%) rubber farmer think that their children education as asset for their future, beside that there are 5 people (33,33%) rubber farmer think that their children education didnât give influence for their children future. Based on the result of this research that had done, it can be conclude that rubber community perception on education consist of positive and negative perspective. Positive perspective can be seen from several of rubber farmer more important childâs education, so that they will work hard for their child education till higher level of study. Negative perspective from rubber farmer can be seen from several of their life assume that childâs education only as something that spent time and money, because education is assumed as a way to get knowledge and a job, whereas it also can be gotten by join to help their parentâs vocation.Â